How pH Modulates the Dimer-Decamer Interconversion of 2-Cys Peroxiredoxins from the Prx1 Subfamily - Morais, Mariana A. B.; Giuseppe, Priscila O.; Souza, Tatiana A. C. B.; Alegria, Thiago G. P.; Oliveira, Marcos A. [UNESP]; Netto, Luis E. S.; Murakami, Mario T. (Amer Soc Biochemistry Molecular Biology Inc, 2015)
2-Cys peroxiredoxins belonging to the Prx1 subfamily are Cys-based peroxidases that control the intracellular levels of H2O2 and seem to assume a chaperone function under oxidative stress conditions. The regulation of their peroxidase activity as well as the observed functional switch from peroxidase to chaperone involves changes in their quaternary structure. Multiple factors can modulate the oligomeric transitions of 2-Cys peroxiredoxins such as redox state, post-translational modifications, and pH. However, the molecular basis for the pH influence on the oligomeric state of these enzymes is still elusive. Herein, we solved the crystal structure of a typical 2-Cys peroxiredoxin from Leishmania in the dimeric (pH 8.5) and decameric (pH 4.4) forms, showing that conformational changes in the catalytic loop are associated with the pH-induced decamerization. Mutagenesis and biophysical studies revealed that a highly conserved histidine (His(113)) functions as a pH sensor that, at acidic conditions, becomes protonated and forms an electrostatic pair with Asp(76) from the catalytic loop, triggering the decamerization. In these 2-Cys peroxiredoxins, decamer formation is important for the catalytic efficiency and has been associated with an enhanced sensitivity to oxidative inactivation by overoxidation of the peroxidatic cysteine. In eukaryotic cells, exposure to high levels of H2O2 can trigger intracellular pH variations, suggesting that pH changes might act cooperatively with H2O2 and other oligomerization-modulator factors to regulate the structure and function of typical 2-Cys peroxiredoxins in response to oxidative stress.